Cooperation or conflict in the Arctic: A literature review - Mikkel Runge Olesen (Danish Institute for International Studies (DIIS), 2014)
Spill-over from the Ukrainian crisis is threatening an otherwise benign international state of affairs in the Arctic, raising once more the question of whether the Arctic is likely to be a scene for cooperation or conflict in the coming years? This question has defined much International Relations research on the Arctic region even before Ukraine. This working paper takes stock of the debates between two groups of researchers, which in the paper are named respectively "warners" and "reassurers", and it argues that the field as a whole has generally become more optimistic regarding the Arctic since 2007. It argues that this optimism is due to the fact that developments in the Arctic since 2007 have generally tended to weaken the case of the "warners". And while recent spill-over from the Ukrainian crisis to the Arctic in 2014 must certainly be seen as a step in the opposite direction, the damaging effects of the crisis need not be a game-changer.
Keywords: 300